(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article examines issues related to the formation of creative thinking in the learning process. The author describes methods for developing students’ creative abilities, considers the theory of inventive problem solving, and provides an example of a creative lesson.